2022
DOI: 10.1002/humu.24331
|View full text |Cite
|
Sign up to set email alerts
|

Detection of revertant mosaicism in epidermolysis bullosa through Cas9‐targeted long‐read sequencing

Abstract: Revertant mosaicism (RM) is a phenomenon in which inherited mutations are spontaneously corrected in somatic cells. RM occurs in some congenital skin diseases, but genetic validation of RM in clinically revertant skin has been challenging, especially when homologous recombination (HR) is responsible for RM. Here, we introduce nanopore Cas9-targeted sequencing (nCATS) for identifying HR in clinically revertant skin. We took advantage of compound heterozygous COL7A1 mutations in a patient with recessive dystroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…At the time of the initial description of RM in a genodermatosis in 1997, RM was considered an extraordinary phenomenon. However, since that initial description, RM has been identified in all major types of EB (Table 1) [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], and, in 2012, we were able to confirm revertant skin patches in all ten Dutch patients with the intermediate type of JEB due to pathogenic COL17A1 variants [ 79 ]. Around the same time, Choate et al demonstrated that each of the multiple healthy ‘confetti-like’ spots in patients with ichthyosis with confetti (IWC) due to germline variants in KRT10 (IWC-I) or KRT1 (IWC-II) represent a separate occurrence of RM in a single keratinocyte clone [ 80 , 81 ].…”
Section: Revertant Mosaicism In Genodermatosesmentioning
confidence: 86%
See 1 more Smart Citation
“…At the time of the initial description of RM in a genodermatosis in 1997, RM was considered an extraordinary phenomenon. However, since that initial description, RM has been identified in all major types of EB (Table 1) [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ], and, in 2012, we were able to confirm revertant skin patches in all ten Dutch patients with the intermediate type of JEB due to pathogenic COL17A1 variants [ 79 ]. Around the same time, Choate et al demonstrated that each of the multiple healthy ‘confetti-like’ spots in patients with ichthyosis with confetti (IWC) due to germline variants in KRT10 (IWC-I) or KRT1 (IWC-II) represent a separate occurrence of RM in a single keratinocyte clone [ 80 , 81 ].…”
Section: Revertant Mosaicism In Genodermatosesmentioning
confidence: 86%
“…Another class of reversion mechanisms involves chromosomal recombination events during mitosis, i.e., gene conversion, intragenic cross-overs, and mitotic recombination. Only a few correction mechanisms identified in EB involve such recombination events [ 26 , 64 , 65 , 70 , 72 , 82 , 86 ], probably because most EB patients in which RM has been identified have biallelic gene mutations where recombination events are less likely to create cells without mutations. In contrast, mitotic recombination is the only reversion mechanism so far identified in the autosomal dominant disorders IWC-I, IWC-II, LK, and PRP [ 80 , 81 , 83 , 84 , 88 , 89 , 90 , 91 ].…”
Section: Molecular Mechanisms Of Revertant Mosaicism In Genodermatosesmentioning
confidence: 99%
“…These sequencers typically generate long to ultra‐long reads. A combination of CRISPR/Cas9 technology and nanopore sequencing has been further shown to enable enrichment and sequencing of specific regions in genomic DNA (gDNA) (Gilpatrick et al, 2020) without PCR procedures or reverse transcription procedures, which can induce artificial homologous recombination (Meyerhans et al, 1990; Natsuga et al, 2022; Negroni et al, 1995). This method is called nanopore Cas9‐targeted sequencing (nCATS) and has been utilized to detect somatic mutations and chromosomal rearrangements (Gilpatrick et al, 2020; Natsuga et al, 2022; Stangl et al, 2020; Watson et al, 2020; Wongsurawat et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…Although regular genetic testing might not always need nCATS, this method can be an option for haplotyping somatic mutations (Natsuga et al, 2022), haplotyping three or more variants in one patient like our study, and identifying repeat expansions (Mizuguchi et al, 2021;Sone et al, 2019). One nCATS experiment costs hundreds of USD, mostly for a MinION flow cell.…”
mentioning
confidence: 99%
“…As most recessively inherited EB carries compound heterozygous mutations, confirmation of RM is necessary before expansion. Identification of RM is challenging, but recently a method has been proposed based on Cas9 enrichment and long-run nanopore sequencing that identify revertant correction resulting from homologous recombination (Natsuga et al 2022). The genetic mechanism behind this phenomenon remains uncertain but it has been associated with back mutations, mitotic recombination, and novel mutations during cell division (Kiritsi et al 2014).…”
Section: Spontaneous Revertant Mosaicismmentioning
confidence: 99%